EFEKTIVITAS PENGGUNAAN MEDIA KARTU KATA BERBASIS KEARIFAN LOKAL TERHADAP KETERAMPILAN MEMBACA PERMULAAN PESERTA DIDIK KELAS II SDN MLALE 1 SRAGEN - Devanur Azizah; Anggit Grahito Wicaksono; Jumanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effectiveness of word card media integrating local wisdom elements in improving the beginning reading skills of second-grade students at SDN Mlale 1 Sragen. A quantitative approach with a quasi-experimental design, specifically the One Group Pretest–Posttest Design, was used. A total of 28 second-grade students participated as research subjects. Data were collected through oral reading tests, classroom observations, and documentation. The test instruments were validated and tested for reliability using Cronbach’s Alpha. The findings revealed an increase in the average score from 54.99 (pretest) to 71.22 (posttest). The results of the paired sample t-test indicated a statistically significant difference (Sig. < 0.001), while the N-Gain score of 0.42 was categorized as moderate. These results confirm that word card media based on local cultural elements is effective in enhancing students' beginning reading skills while also creating a more meaningful and engaging learning environment.